2019
DOI: 10.1088/2399-6528/ab3e2b
|View full text |Cite
|
Sign up to set email alerts
|

Force and current in a contact gap between single highly resistive particles: experimental observations

Abstract: In case of electrical conduction through highly resistive dust layers, the generation of electrostatic adhesion force is strongly coupled to the mechanism of electrical (current) transport in the solid. High field strengths lead to a significant increase of the adhesive force. Here, more insight into the underlying mechanisms is given by experiments on the microscopic scale. An experimental arrangement is described which allows to study a particle pair subject to a strong electric field. Both the current and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Experimental investigations on current transport across narrow gaps between dielectric (glass) particles (Vora et al 2019) have shown that self-sustaining or self-amplifying gas discharges cannot develop (in air at ambient pressure) with pore sizes below about 2 µm. With dielectric materials, the supply of electrons is limited due to the high resistivity of the material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental investigations on current transport across narrow gaps between dielectric (glass) particles (Vora et al 2019) have shown that self-sustaining or self-amplifying gas discharges cannot develop (in air at ambient pressure) with pore sizes below about 2 µm. With dielectric materials, the supply of electrons is limited due to the high resistivity of the material.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the deposited NPs might be seen as a dielectric material which nevertheless allows a certain amount of current transport by injected electrons or holes. Possibly the behavior of such materials can resemble to the behavior of conductive particles (Vora et al 2019). This allows the build-up of high fields which allow either the thermionic field emission of free electrons (on the cathode side only) or the development of microscopic, intermittent gas discharges.…”
Section: Current-voltage Characteristicsmentioning
confidence: 99%